Synthesis, Crystal Structures and Urease Inhibition of Mononuclear Copper(II) and Nickel(II) Complexes with Schiff Base Ligands - Jian Jiang; Peng Liang; Huiyuan Yu; Zhonglu You (Acta Chimica Slovenica, 2022)
Three mononuclear copper(II) and nickel(II) complexes, [Cu(L1)(NCS)(CH3OH)] (1), [Cu(L2)(NCS)] (2) and [Ni(L2)(N3)] (3), where L1 and L2 are the monoanionic forms of the Schiff bases N'-(pyridin-2-ylmethylene)picolinohydrazide (HL1) and 4-methyl-2-(((pyridin-2-ylmethyl)imino)methyl)phenol (HL2), have been prepared and characterized by elemental analysis, IR and UV-Vis spectroscopy, as well as single crystal X-ray diffraction studies. The Cu atom in complex 1 is in a square pyramidal coordination, with the three N atoms of the ligand L and the N atom of the thiocyanate ligand in the basal plane, and with the methanol O atom at the apical position. The Cu and Ni atoms in complexes 2 and 3 are in square planar coordination, with the three donor atoms of the Schiff base ligands and the terminal N atoms of thiocyanate and azide ligands. Complexes 1 and 2 inhibit the Jack bean urease with IC50 value of 0.33±0.12 and 0.39±0.10 μmol L–1, respectively. Molecular docking study was performed to investigate the interaction between the complexes and the enzyme.